Constitutional Analysis of Research Ethics Review Laws: The United States and Beyond - Chen, Chung-Lin (Science and Technology Law Review, 2015)
The ethics review mechanism has long been accepted as a safeguard for the rights and welfare of human research participants. However, where the ethics review requirement is compelled by law, the constitutional concern of free research arises. To respond to this constitutional concern, this Article argues that the authority of research ethics committees should be cautiously designed to tailor to the protection of participants and avoid undue intervention in research content. The current federal regulation vests overly broad discretion to institutional review boards (IRBs) and constitutes a content-based prior restraint. This Article therefore urges a reform to achieve appropriate constraint of IRB review power, which would render the regulation constitutional and legitimize expanding the IRB requirement to encompass equal application regardless of funding source.